South African public memorials of World War One. A historical view of processes in public memorialisation through symbolic content, with particular reference to Cape Town - Binckes, Helen (Department of Historical Studies, 2014)
The dissertation is an attempt to unravel the sentiments which are embodied in war memorials by examining the conditions and events of the war as a way into understanding the motivations of the survivors, who brought them into being. The memorials in Cape Town do not exist in isolation, and therefore it was expedient to refer to both the art and architecture of death in general, through modern history up to contemporary prototypes, particularly the war memorials in northern Europe. The symbolic content is of paramount importance. Photographs, in the Appendix, will visually illustrate many points which are referred to during the course of the study. Each memorial embodies its unique set of cues for articulating an interpretation. To do this it is necessary to present the background of the War, 1914-1918/191 in terms of the intricacies of South African social and political dynamics: the war lives at the Front and the home lives in Cape Town. Initial information came with the viewing of the memorials in their present localities, so that the dialogue of interpretation between the art object-memorial and the viewer, could be set in motion. Out of that dialogue came the structure for the study of Cape Town memorialisation.